Antioxidant Activity and Phenolic Composition of Amaranth (Amaranthus caudatus) during Plant Growth - Magdalena Karamać; Francesco Gai; Erica Longato; Giorgia Meineri; Michał A. Janiak; Ryszard Amarowicz; Pier Giorgio Peiretti (MDPI AG, 2019)
The antioxidant activity and phenolic composition of the aerial part of Amaranthus caudatus at seven stages of development were investigated. Total phenolic content, ABTS•+, DPPH•, and O2•− scavenging activity, ferric-reducing antioxidant power (FRAP), and Fe2+ chelating ability were evaluated. The phenolic profile was characterized by 17 compounds. Rutin was predominant in all growth stages, although its content, similar to the quantity of other phenolics, changed during the growth cycle. Flavonols were most abundant in the plants of early flowering and grain fill stages. In contrast, the highest content of hydroxycinnamic acid derivatives was found in the early vegetative stage. The results of antioxidant assays also showed significant differences among plant stages. Generally, the lowest antioxidant activity was found in the shooting and budding stages. Significantly higher activity was observed in amaranths in earlier (vegetative) and later (early flowering and grain fill) stages, suggesting that plants in these stages are valuable sources of antioxidants.